GAMBARAN RADIOGRAF PADA PENYAKIT PERIODONTAL - Dewi Saputri (Dentistry Faculty, 2018)
Periodontal disease is an infectiuos disease that happen of the periodontal tissue. In order to see theprogress of periodontal disease, a proper examination is needed in which it includes clinical andsupporting examination. One of a supporting examination in diagnoses periodontal disease is radiographexamination. Radiographic appearance provide important information since it can show an image that can not be seen by clinical examination like the length of the root, bone height, patterns of bone destructionand others abnormalities of the periodontal tissue except gingival tissue. Radiographic appereance is avaluable in the diagnoses of periodontal disease, treatment planning, determination of prognosis andevaluation of the outcome of treatment Keywords : Periodontal Disease, Supporting Examination, Radiographic Appereance